Climate resilience through bioeconomy: A mixed-methods protocol for assessing adaptation policies in rural settlements on the Amazon - Daniel Silva; Larissa Alves; Naurinete Reis; Maclem Erane Gonçalves dos Santos; Emilio Mendes; Vitor Castro (PLoS ONE, 2026)
Introduction Climate change intensifies social, economic, and environmental vulnerabilities in Amazonian rural communities, where dependence on natural resources and limited institutional capacity constrain adaptation. The bioeconomy is often proposed as an alternative pathway for sustainable development, yet empirical evidence of its role in resilience remains scarce. Objective This study protocol presents a mixed methods design to evaluate climate adaptation policies and community resilience strategies in agrarian reform settlements, rural territories created through Brazil’s land redistribution program, in Pará, Brazil. Although centered on a regional case, the protocol is structured to generate insights applicable to other socioecologically vulnerable rural contexts in the Amazon and comparable regions worldwide. Methods The study will be conducted in 15 municipalities across the three regional superintendencies of the National Institute for Colonization and Agrarian Reform. The design integrates (i) secondary data on socioeconomic, climatic, and policy indicators; (ii) semi-structured interviews with municipal managers (n = 1–3 per municipality); (iii) focus groups with community leaders (n = 8–12 per settlement); and (iv) household surveys (n = 20–50 families per settlement). Primary outcomes include the Income and Livelihood Diversification Index (ILDI), Climate Vulnerability Perception Scale (CVPS), Bioeconomy Engagement Index (BEI), and Reported Adaptive Capacity Index (RACI). Secondary measures include the Adaptation Strategy Diversity Index (ASDI) and a Municipal Climate Engagement Typology (MCET). Quantitative analyses will employ multilevel linear and generalized linear models (LMM/GLMM), while qualitative data will be analyzed through reflexive thematic analysis, with final integration achieved via a triangulation framework. Expected results This study will generate a comprehensive framework integrating indicators of vulnerability, adaptive capacity, and bioeconomy engagement across agrarian reform settlements in the Eastern Amazon. By combining household surveys, qualitative fieldwork, and municipal-level policy analysis, the protocol provides a transparent, replicable approach for assessing local climate adaptation processes. The study is designed to inform municipal and state policymakers, support the strengthening of local adaptation initiatives, and contribute evidence relevant to Sustainable Development Goals (SDGs 2, 13, and 15).